2016
DOI: 10.4184/asj.2016.10.6.1100
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Posterior Lumbar Interbody Fusion Using Stand-Alone Ray Threaded Cage for Degenerative Disk Disease: A 20-Year Follow-Up

Abstract: Study DesignRetrospective study.PurposeTo analyze outcomes of posterior lumbar interbody fusion (PLIF) stand-alone cages.Overview of LiteraturePLIF for degenerative disk disease using stand-alone cages has lost its popularity owing to implant-related complications and pseudoarthrosis.MethodsWe analyzed the records of 45 patients (18 women, 27 men), operated between January 1994 and December 1996, with a mean follow-up of 18 years 3 months (20 years 3 months–22 years 3 months). Clinical outcomes were measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Our results of FJR compare favorably with monosegmental lumbar fusion concerning leg and back pain, 15 as well as improvement of ODI score. 21 The revision rate in our small series of FJR was 15.4%, and compares to large series of rigid lumbar fusions with 19.3% after 4 years, mostly due to adjacent level disease. 22 A large retro-spective cohort study of 912 cases revealed a 31% prevalence for adjacent level surgery after 10 years.…”
Section: Fjr Versus Rigid Fusionsupporting
confidence: 45%
“…Our results of FJR compare favorably with monosegmental lumbar fusion concerning leg and back pain, 15 as well as improvement of ODI score. 21 The revision rate in our small series of FJR was 15.4%, and compares to large series of rigid lumbar fusions with 19.3% after 4 years, mostly due to adjacent level disease. 22 A large retro-spective cohort study of 912 cases revealed a 31% prevalence for adjacent level surgery after 10 years.…”
Section: Fjr Versus Rigid Fusionsupporting
confidence: 45%
“…Moreover, Costa et al [1] argue that when placing stand-alone cage, the facet joints are preserved and the destruction of the posterior and facet joint ligaments and of the endplates is minimal, conditions that are crucial to successful bone fusion. On the other hand, long-term follow-ups [79] have obtained that PLIF stand-alone cages were associated with good clinical outcomes but although the fusion rate was excellent, maintenance of disc heights and lordotic alignment were not achieved in the long term. Therefore, there are still pending questions.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The CBT approach may reduce injury or trauma to the neurovascular structures in close proximity to the pedicle; (3) The CBT may also avoid injury to the medial branch nerves, which arise from the dorsal rami of each lumbar spinal nerve 24) . It has been reported that MIDLF results in less damage to the multifidus muscle compared to PLIF 15) .…”
Section: Discussionmentioning
confidence: 99%
“…Lateral flexion-extension radiography and computed tomography (CT) scans were obtained at the 12-month postoperative follow up to evaluate bone fusion status. There are many analyses for spinal instability 3,12,16,30) . A stable spine was defined as no or less than 2 mm translation and no angulation in the flexion-extension radiographs of patients.…”
Section: Radiographic Evaluations and Clinical Outcomesmentioning
confidence: 99%